The Four ‘Cornerstones’ of Tourism Geography - Kowalczyk, Andrzej; Kulczyk, Sylwia (Turyzm/Tourism, 2008)
There are four theoretical concepts in geography for describing spatial relations – space, environment, place and landscape. All of them are useful in tourism geography research but they are connected to differing methodological approaches